(3eUHGM GdXdeGJ aj cTa eYGfi GdeDKQGJs - (3Ydj Hf eMeO Hf CMeO GdHcQj,J (B882 (3g` s
(3ChdgG (B:s
(3bGd GdTjN CHh eMeO GdMSf Hf eMeO Hf GdMSf GdQUGU GdMeO ddg GdNGdb GdCQVjf hGdSeGhGJ GdMeO gh GdKfGA GdMSf , hjbGd dg CjVkG eOMkG s
(3BNQgG (B:s
(3bhdg (B: (3agPg WQjbI Gdbhd ai MbGFb GdeDKQGJ heG jLQi eLQGgG hbO HjfG GdcdGe ai Pdc Ydi WQjb GdELeGd Ohf GdJaUjd gPG BNQ GdcJGH Je GdeNJUQ s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI eUMMIs
(3cJHJ GdahGJM HGdSejc cJHJ HOQ GdOjf eMeO Hf YHO Gddg Hf GdgGOi Hf eMeO GdeMQGHi Ydi ZGTJgG ebGHdI eDQNI (B1074(3g` s
(3Ydi WQJgG JedcGJ s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdadSaI hGdefWbs